2022
DOI: 10.1088/1755-1315/961/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

The Establishing of Geospatial Database for Agricultural Lands of Islamic WAQF In Iraq: Case Study Babil Province

Abstract: In numerous countries, one of the most significant pieces of background records is a religious endowment that usually called (WAQF), which have a cultural, and economic value. For instance, in Iraq, religious endowments comprise a large number of dispersed real estates and lands usually required effective administration methods. Agricultural lands that belonged to religious endowments lack of sufficient systems, which are combined statistical and spatial information in terms of spatial monitoring and informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The extrapolation of the linear section of the curve to the (αhν) 2 = 0 point gives the bandgap energy, which is found to be in the range of (4.25-4.9) eV depending on the laser fluence. The optical energy decreases as laser fluence increases due to the formation of smaller particles at low laser fluence, which can be attributed to the quantum size effect [73][74][75]. These results are consistent with TEM results that revealed that the bandgap energy decreased as the laser fluence increased due to increasing particle size with laser fluence, as shown in figure 6.…”
Section: Resultssupporting
confidence: 87%
“…The extrapolation of the linear section of the curve to the (αhν) 2 = 0 point gives the bandgap energy, which is found to be in the range of (4.25-4.9) eV depending on the laser fluence. The optical energy decreases as laser fluence increases due to the formation of smaller particles at low laser fluence, which can be attributed to the quantum size effect [73][74][75]. These results are consistent with TEM results that revealed that the bandgap energy decreased as the laser fluence increased due to increasing particle size with laser fluence, as shown in figure 6.…”
Section: Resultssupporting
confidence: 87%
“…As of now, the best solution available is to integrate "GIS and RS" Techniques to select safe the environment, socially acceptable, and economically viable village sites. GIS is useful because of its unique ability to do integrate spatially and attribute data analysis [8] to automatically produce maps of candidate sites thereby reducing the cost and time involved in the process [7]. The RS technology can provide up-to-date spatial data.…”
Section: Introductionmentioning
confidence: 99%